Processing different types of iconicity in Chinese transferred epithet comprehension: An ERP study - Liao, Qiaoyun; Gao, Mengting; Weng, Xin; Hu, Quan (Frontiers in Psychology, 2022)
The present study examined the neurocognitive mechanism of Chinese transferred epithet comprehension by employing ERP technique from the perspective of Iconicity of Markedness. Participants were required to read materials with different types of semantic markedness, namely unmarked linguistic expression (literal sentences) and marked linguistic expression (transferred epithets), and then judge whether the targets were words or pseudo-words. In terms of semantic markedness, the targets are words reflecting the unmarked semantic meaning of literal sentences and marked semantic meaning of transferred epithets respectively. The target words after transferred epithets elicited a larger N400 and a smaller LPC than those in literal sentences. These results suggest that processing sentences with marked and unmarked iconicity involve different neural mechanisms, with the former requiring more cognitive efforts to extract the similarity features.